Vitamin E status, glutathione peroxidase activity and the effect of vitamin E supplementation in children with thalassemia - U. Suthutvoravut (2018)
Vitamin E and selenium statuses were studied in thalassemic children in comparison with 16 normal controls. Twelve Hb H disease, 46 betathal/Hb E and 7 beta-thal major patients had lower plasma vitamin E level than controls but plasma vitamin E/total lipids ratio of Hb H disease subjects was not different from normal. Twelve Hb H disease and 33 beta-thal/Hb E patients had normal RBC Se but increased RBC GSH-Px activity. Ten vitamin E-deficient thalassemic subjects had been supplemented with 200 mg of oral vitamin E for 4-8 weeks. After supplementation, their plasma vitamin E increased and H2O2 hemolysis decreased to normal values. Their RBC GSH-Px activity also decreased but hematocrit did not change significantly. The results demonstrate that some types of thalassemic patients have vitamin E deficiency and support that vitamin E and selenium have related functions in the prevention of RBC oxidation. Vitamin E supplementation increased RBC resistance to oxidative damage.